C. vulgaris growth batch tests using winery waste digestate as promising raw material for biodiesel and stearin production. (December 2021) - P., Scarponi; F.C., Izzo; M., Bravi; C., Cavinato
Highlights: Adapted C. vulgaris showed growth capacity on winery waste digestion effluent. Batch growth test with 20% of digestate shows no inhibition effects. C. vulgaris biomass concentration of 1.36 ± 0.09 g l −1 was obtained. Winery waste digestate promoted C. vulgaris lipid storage up to 28%. Lipid characterization showed 65%w/w of oleic acid and 0.15%w/w of linolenic acid. Abstract: The recovery of high added value compound from waste stream is fundamental to keep biotechnological processes sustainable. In this study, anaerobic digestion of two highly produced organic waste was integrated with microalgae-based processes both to treat liquid digestate and recover high value compounds. Chlorella vulgaris growth was assessed for lipids accumulation and subsequent recovery, using two types of digestate: organic waste and sewage sludge digestate (DIG-OFMSW) and wine lees digestate (DIG-WL). Growth tests were carried out in batch mode and results showed a slightly higher final biomass concentration from DIG-WL (1.36 ± 0.09 g l −1 ) compared to DIG-OFMSW (1.05 ± 0.13 g l −1 ) and a clearly different lipids accumulation yield (28.86 ± 0.05% in DIG-WL compared to 6.1 ± 0.2% of DIG-OFMSW, on total solids). Lipid characterization showed a high oleic acid accumulation (69.52 ± 0.50%w/w in DIG-WL) that positively influence biodiesel properties and a low linolenic acids content (below 0.30%w/w) that comply with European law EN14214 for biodiesel (linolenic acid content lower than 12%w/w). In addition, due to the high concentration of palmitic and stearic acids detected at the end of test, this oil can be used as new substrate to produce stearin, normally produced from palm oil.